Uji Efektivitas Serbuk Cangkang Keong Mas plus Trichoderma spp. terhadap serangan Nematoda Puru Akar (Meloidogyne spp.) Pada Tanaman Seledri (Apium graveolens L.) - Tegar Imani; Elly Liestiany; Noor Aidawati (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Celery (Apium graveolens L.) is a cultivated plant that has a distinctive aroma and high economic value and has the potential to be developed in Indonesia. One of the plant pest organisms (OPT) that can affect the quality and quantity of celery production is the root knot nematode caused by Meloidogyne spp. This study aims to determine the effectiveness of golden snail shell powder plus Trichoderma spp. in influencing root knot nematode (Meloidogyne spp.) attacks on celery plants (A.graveolens L.). This study was designed using a one-factor Completely Randomized Design (CRD). The factors tested were the effect of giving golden snail shell powder plus Trichoderma spp., giving golden snail shell powder and giving Trichoderma spp. The treatment was carried out 6 times and repeated 4 times with observation parameters, namely attack intensity, nematode population, number of stems and fresh weight of celery plants. The results showed that the administration of golden snail shell powder plus Trichoderma spp. can influence the intensity of root node attacks and reduce nematode populations in the soil around the roots, as well as have a significant effect on the number of leaves (stalks) and fresh weight of celery plants